KARAKTERISTIK PHISIK DAN STRUKTUR MIKRO KOMPOSIT LOGAM ALUMINIUM-GRAFIT HASIL PROSES METALURGI SERBUK - Pramono, Agus; Junus, Salahuddin (ROTOR, 2011)
Composite graphite alluminium represent the material with the nature of good mechanic and also light mass so that able to economize the fuel. Composite graphite alluminium made with the method of powder metallurgy with the step of making mixing powder, compaction and sintering. Composite this upon which for the application of bearing self-lubricating, so that have to measure up to the high mechanic. Nature of the will not be reached when matrix by reinforce do not tying. To improve that matter, need the drenching and detention of time sintering. This research use the volume faction 92% alluminium and 8% graphite and 10% Magnesium as wetting agent. At drenching process conducted by a graphite veneering as reinforce use the condensation HNO3 to yield metal oxide which variation 20 ml, 40 ml and 50 ml HNO3 with the time sintering 15 minute, 30 minute and 60 minute. At this research done by examination density, porosity and micro structure perception. Result of research indicate that the time hold up the sintering progressively mount hence density go up and porosity descend so that yielded a closer micro structure but accompanied also deffect becoming initial crack from composite material, optimum variable yielded at 20 ml HNO3 and time sinter 60 minute with the value density 2,48 g /cm3 and porosity 17,2 %. Keywords: composite, sintering and powder metallurgy